Faith and reason in the Catholic intellectual tradition - Sagut, Joel C.; Co, Alfredo P.; Aguas, Jove Jim S.; Baybado, Pablito A. Jr.; Ojoy, Virgilio A.; Basas, Allan A.; Flores, Danilo R.; Sweetman, Brendan; Weckert, John (España, Manila, Philippines University of Santo Tomas Publishing House, 2022)
"Joel C. Sagut ruminates on the tensions between faith and reason, and their ultimate mutuality in Catholic thought. Renowned Filipino scholar Alfredo P. Co’s new work, “Doing Philosophy in the Philippines: The Thomasian Collection (1951-1959) Volume II,” was also recently released and launched alongside its first volume, which both collect scholarly articles on the condition of Filipino philosophy, and the trajectories of humanistic thought in the Catholic intellectual tradition. Joining them is “Faith and Psychology: A Walk-Through on the Filipino Basic Ecclesial Communities” by Milagros C. Arrevillaga, a close look into Philippine ecclesial communities and the psychology of communal living rooted in faith."
A preliminary reflection on Fides et Ratio and the evangelization of the East in the 21st century / Alfredo P. Co -- The complementarity of faith and reason in Christianity according to Fides et Ratio / Jove Jim S. Aguas -- From phenomenon to foundation: Fides et Ratio's prospects for dialogue and peacebuilding / Pablito A. Baybado, Jr. -- Desacralizing the Christian proclamation in the global city / Virgilio A. Ojoy, O.P. -- Journeying with the poor in their ongoing struggle for recognition: exploring the critical potential of PCP II's church of the poor / Allan A. Basas -- The exercise of the Potestas Vicaria of the Roman pontiff: perfect and harmonious interaction of fides, ratio atque Ius / Danilo R. Flores -- Some reflections on the relationship between religion and science, especially evolution / Brendan Sweetman -- Trust and technology / John Weckert.
Includes bibliographical references (pages 165-176)
Keywords: Faith and reason -- Christianity